Pengaruh Beban Kerja dan Stres Kerja terhadap Cyberloafing dengan Lingkungan Kerja Sebagai Variabel Intervening : Studi pada UD Saimunjaya - Ainin Fitri Ramadhani; Imama Baidlowi; Kasnowo Kasnowo (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
The rapid development of information technology has had a significant impact on the world of work. One emerging phenomenon is cyberloafing, which is the use of the internet by employees for personal purposes during work hours. This phenomenon can reduce productivity if not managed properly. This study was conducted at UD Saimun Jaya with the aim of analyzing the influence of workload and job stress on cyberloafing behavior, as well as assessing the role of the work environment as an intervening variable. The research method used a quantitative approach with a survey technique, in which questionnaires were distributed to 35 employees as respondents. Data analysis was carried out through multiple linear regression, F-test, t-test, and path analysis with the help of SPSS software. The results showed that workload and job stress have a positive and significant influence on cyberloafing. However, the work environment does not mediate the relationship between workload and cyberloafing. Conversely, in the relationship between work stress and cyberloafing, the work environment acts as a partial mediator. These findings emphasize the importance of management attention to proportional workload distribution, appropriate work stress management, and the creation of a conducive work environment to suppress cyberloafing behavior. This finding suggests that organizational strategies should not only focus on workload distribution but also emphasize stress management and a supportive work environment. The practical implications of this research provide insights for small companies, particularly in formulating effective human resource management strategies. By reducing excessive workloads, minimizing stress levels, and building a healthy work environment, companies can control cyberloafing behavior and maintain optimal work productivity.